IDENTIFYING REASONS FOR STUDENTS LEARNING ACTIVITY IN VOCATIONAL TECHNICAL EDUCATION - PLĂMĂDEALĂ, Vasile; SUGAC, Olga; GOIAN, Vladimir (Journal of Social Sciences)
The fundamental changes taking place in socio-economic life, both in the country and abroad in recent years, have required a revision of priorities in the system of training engineering personnel and have identified one of the most important goals of a higher technical school – the preparation of the future engineer for independent professional and creative activity, as a necessary condition for the formation of the student's personality, motivated by the creative realization of personal potential, professional skills and abilities. Among the psychological and pedagogical problems of higher education, the most significant is the problem of developing the educational motivation of students, since a high level of educational motivation is one of the most effective means of increasing the efficiency and quality of the educational process. The article includes theoretical and empirical research focused on learning motivation among students of the study programs of Engineering and Management in Transport and Automotive Transport Engineering within the Faculty of Mechanical, Industrial and Transport Engineering of the Technical University of Moldova, identifying the specifics of the dominant learning motivation depending on the year and study program, determining students' attitude towards the objects of the curriculum from the perspective of interest, importance and understanding, and establishing the factors influencing students' learning motivation.